AKAD MUDHARABAH DALAM LEMBAGA KEUANGAN SYARIAH - Dhamar, Sya'idun (Commodity : Jurnal Perbankan dan Keuangan Islam, 2023)
The presence of Islamic banks that use a profit sharing system, in realitybetween banks based on sharia and banks with conventional principles aresimilar, only differing in terms of terms, namely conventional banks use an interest system and sharia with profit sharing. The mudharabah contract implemented in Islamic banks has changed and is not like the initial concept in fiqh which was based on justice, but in Sharia banks, in its application, if there is a loss, it will be borne by the borrower. This research will explain in detail the application of mudharabah theoretically and in reality as it actually occurs using a literature review research model. The results of this research are concerns about losses that will be borne by the banking sector as the owner of the funds. Meanwhile, customers are not charged losses if the business they run does not experience a profit.